Development of a partner preference test that differentiates between established pair bonds and other relationships in socially monogamous titi monkeys (Callicebus cupreus). Issue 3 (31st July 2015) - Carp, Sarah B.; Rothwell, Emily S.; Bourdon, Alexis; Freeman, Sara M.; Ferrer, Emilio; Bales, Karen L.
Abstract : Partner preference, or the selective social preference for a pair mate, is a key behavioral indicator of social monogamy. Standardized partner preference testing has been used extensively in rodents but a single test has not been standardized for primates. The goal of this study was to develop a partner preference test with socially monogamous titi monkeys ( Callicebus cupreus ) adapted from the widely used rodent test. In Experiment 1, we evaluated the test with pairs of titi monkeys ( N = 12) in a three‐chambered apparatus for 3 hr. The subject was placed in the middle chamber, with grated windows separating it from its partner on one side and an opposite sex stranger on the other side. Subjects spent a greater proportion of time in proximity to their partners' windows than the strangers', indicating a consistent preference for the partner over the stranger. Touching either window did not differ between partners and strangers, suggesting it was not a reliable measure of partner preference. Subjects chose their partner more than the stranger during catch and release sessions at the end of the test. In Experiment 2, we compared responses of females with current partners ( N = 12) in the preference test with other relationship types representing former attachment bonds ( N = 13) and no attachment bond ( N = 8). Only females from established pair bonds spent significantly more time near their partner's window compared to the stranger's indicating that this measure of preference was unique to current partners. Other measures of preference did not differentiate behavior toward a current partner and other relationship types. This test reproduces behavioral patterns found in previous studies in titi monkeys highlighting the accuracy of this new partner preference test. This test can be used as a standardized measure of partner preference in titi monkeys to quantitatively study pair bonding and evaluate factors influencing partner preference. Am. J. Primatol. 78:326–339, 2016. © 2015 Wiley Periodicals, Inc.